Kontribusi Self Acceptance terhadap Fear of Intimacy pada Mahasiswa yang Orang Tuanya Bercerai di Kota Padang - Meunasah, Oca Ryanda; Mardianto, Mardianto (Lembaga Yasin AlSys, 2025)
Students are individuals aged 18 to 25 who are in the early adulthood phase, which is a period in an individual's life to adjust to new life patterns and new social expectations, as well as to take responsibility for their development and life. This study aims to determine whether self-acceptance contributes to fear of intimacy among students whose parents are divorced in the city of Padang.This research is a correlational quantitative study. The sampling technique used in this study is purposive sampling with a sample size of 110 students, collected over a week from January 9-15 2025. The data for this research were obtained using a Likert scale model and then analyzed with simple linear regression analysis. The results of this study indicate that self-acceptance contributes to fear of intimacy among students whose parents are divorced in the city of Padang by 20.7%.